Evaluation of the reduction roast – magnetic separation process to upgrade low-grade ferruginous manganese ore fines - Cromarty, Robert (University of Pretoria, 2023)
Dissertation (MEng (Metallurgical Engineering))--University of Pretoria, 2022.